PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN KUALITAS APARATUR PEMERINTAH DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus Pada Pemerintah Kabupaten Bima, NTB) - Ramdhani Nur Safitri; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study is to determine whether there is an influence of the application of government accounting standards (SAP) and the quality of local government apparatuses on the quality of financial statements presented by government organizations. The population in this study are civil servants (PNS) who work in the Bima Regency Government. The research sample of 47 respondents. The sampling method uses Purposive Sampling Method.In conducting data analysis, using multiple linear regression analysis with the variable Implementation of Government Accounting Standards (SAP) and the Quality of Local Government Apparatus as an independent variable. Variable Quality of Financial Statements as the dependent variable. Based on the results of research conducted prove that the Application of Government Accounting Standards (SAP) and the Quality of Local Government Apparatus has a partial influence on the Quality of Financial Statements. The results also showed that it also had an influence on the Application of Government Accounting Standards (SAP) and the Quality of Local Government Apparatuses had a simultaneous influence on the quality of the Bima Regency Government Financial Statements.Keywords: Application of Government Accounting Standards, Quality of LocalGovernment Apparatus, Quality of Financial Statements.